ANALISIS SOSIOLOGI KARYA SASTRA DALAM NOVEL “DIA, TANPA AKU” KARYA ESTI KINASIH: KAJIAN SOSIOLOGI PENGARANG DAN SOSIOLOGI SASTRA - Ni Made Widaswari; I Nyoman Adi Susrawan; Dewa Gede Bambang Erawan (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2022)
This research is a qualitative descriptive study that aims to analyze the study of the sociology of the author and the sociology of literature in terms of the author's social status and the sociology of literature from the reader's perspective and its social influence in the novel